WC-base cemented carbides with partial and total substitution of Co as binder: Evaluation of mechanical response by means of uniaxial compression of micropillars. (November 2019) - Sandoval, D.A.; Rinaldi, A.; Notargiacomo, A.; Ther, O.; Roa, J.J.; Llanes, L.
Abstract: The influence of the chemical nature of the metallic binder on the plastic deformation of cemented carbides was studied. Three different cemented carbide grades - WC-Co, WC-CoNi and WC-NiMo - with similar microstructural characteristics (binder content and carbide grain size) were investigated. Mechanical response was evaluated by means of uniaxial compression of micropillars, and tests were carried out in-situ in a FESEM with a nanoindenter equipped with a flat-diamond punch. After uniaxial compression, inspection of deformation phenomena was done at both surface and bulk of micropillars through scanning and transmission electron microscopy, respectively. It is found that yielding phenomena and strain hardening increase as Co is totally substituted by a NiMo alloy, while contrary effect results from partial replacement of Co with Ni. Relative differences are directly linked to intrinsic ductility of the metallic phase and operative plastic deformation mechanisms. Moreover, for the three materials studied, stress-strain responses show pronounced yielding events related to glide at WC/WC interfaces. Although they are discerned at different stress levels, estimated values of sliding resistance of WC/WC boundaries are found to be alike for the three grades studied. Highlights: Early irreversible deformation is linked to plastic activity within metallic binder. Plastic deformation of binder intrinsically depends on its chemical nature. Deformation ability of binder is extrinsically affected by constraining from WC. Binder chemical nature does not seem to affect WC/WC gliding resistance.